UPAYA ORANG TUA DALAM MENGEMBANGKAN KREATIFITAS ANAK USIA DINI DI TRIMULYA KECAMATAN TIMPEH KABUPATEN DHARMASRAYA - Rahmawati, Dewi; Kasih, Fitria; Zaini, Ahmad (Bimbingan dan Konseling, 2013)
The problems in this research based on phenomena that researcher found in the field. the students not active in learning process, old fellow not yet can in developing its child creativity. Pursuant to researcher the mentioned lift problems of research about: How old fellow effort in developing age child creativity early in Trimulya Kecamatan Timpeh Kabupaten Dharmasraya seen from activity develop condition and creativity influencing creativity. This research aim to description (1) Effort old fellow in developing age child creativity is early seen from activity develop creativity (2) Effort old fellow in developing age child creativity is early seen from condition of able to influence in developing creativity.This research represent descriptive research which try depict situation as it is. This Research population is to include;cover entire/all age child early in Trimulya Kecamatan Timpeh amounting to counted 47 people. Research Sampel total sampling. Become sampel in this research counted 47 child. Data collecting in research use enquette, while data analysis the used is descriptive statistic by wearing percentage formula.Result of this research lay open that (1) Effort old fellow in developing age child creativity is early seen from activity develop creativity reside in at good criteria (2) Effort old fellow in developing age child creativity is early seen from condition of able to influence in developing creativity reside in at good criterion. Pursuant to result of research above, researcher can conclude that old fellow effort in developing age child creativity early reside in at good criteria. Writer suggest to old fellow in developing age child creativity early can be done/conducted by process word.